Efek Anti-tifoid Minyak Atsiri Temu Putih (Curcuma zedoria Rosc.) pada Tikus (Rattus norvegicus L) yang Terinfeksi Salmonella typhi - Rina Yanti Eff, Aprilita (Pharmaceutical Sciences and Research, 2018)
Temu putih (Curcuma zedoria Rosc.) contains essential oils that have antibacterial effects, in which one of the example is against Salmonella typhi. The aim of this study is to find out the anti-typhoid effect of essential oil from temu putih in rat infected by Salmonella typhi using widal test. The study was conducted experimentally. Rats were divided into six groups, i.e., normal control group, negative control group which was given PGA 10%, positive control group, which was administered chloramphenicol suspension 20 mg / 250 g BB, experiment group 1, 2 and 3 which were administerd emulsion essential oil at a dose of 14 mg / mL, 28 mg / mL, 42 mg / mL, respectively. Antibody titer was measured on day 1 (Widal test I), day 8 (Widal test II) and on day 14 (Widal test III). After the Widal test I, rats were induced Salmonella typhi bacterial suspension for 7 days orally, except for normal control group, and followed by administration of treatment 3 times daily for 7 consecutive days according to the group. The result of Widal test I shows negative value on all groups of animal test, whereas Widal test II result shows an increase of titer antigen Salmonella typhi O and H ranging from 1/80 up to 1/320 in rats induced by Salmonella typhi bacteria. Essential oil from Curcuma zedoria Rosc at doses of 14 mg / mL, 28 mg / mL and 42 mg / mL decreased the Salmonella typhi O and H antigen titer in rats infected by Salmonella typhi and has anti-typhoid effect.